Environmental Groundwater Vulnerability Assessment in Urban Water Mines - Afonso, Maria José (2017)
A multidisciplinary approach was developed to estimate urban groundwater vulnerability to contamination combining hydrogeology, hydrogeochemistry, subterranean hydrogeotechnics, groundwater ecotoxicology and isotope tracers. Paranhos and Salgueiros spring waters in Porto City were used as a case study. Historical and current vulnerability scenarios were compared using hydrogeological GIS-based modelling. Potential contamination sources were mapped around the spring galleries. Most of these were point sources and their potential contamination load was moderate. The ecotoxicological assessment indicated a low acute toxicity potential. Groundwater radionuclides appeared to be mainly controlled by geological factors and biomineralisation. Vulnerability maps suggest that most of the area has a moderate to low vulnerability to contamination. However, some surface sources such as sewage systems cause contamination and contribute to increased vulnerability. This integrated approach was demonstrated to be adequate for a better knowledge of urban hydrogeological processes and their dynamics, and highlighted the importance of a vulnerability assessment in urban areas.